Risk of post-fracture pneumonia and its association with cardiovascular events and mortality in adults with intellectual disabilities - Whitney, Daniel G.; Erickson, Steven R.; Berri, Maryam (Frontiers in Psychiatry, 2023)
Objective Fragility fractures are associated with an increased risk of pneumonia, which is a leading cause of death in adults with intellectual disabilities; however, the timing and complications of post-fracture pneumonia are underinvestigated. The objectives of this study were to determine the 30-day pneumonia rate post-fracture and the association of post-fracture pneumonia with mortality and cardiovascular events among adults with intellectual disabilities. Methods This retrospective cohort study was conducted using Medicare and commercial claims from 01 January 2011 to 31 December 2016. Incidence of pneumonia 30 days after a fragility fracture among adults ≥18 years old with intellectual disabilities (Fx cohort) was compared to the incidence among matched adults with intellectual disabilities without fractures (w/oFx cohort) and the general population of patients with an incident fragility fracture (GP+Fx). For the Fx cohort, Cox regression was used to examine the adjusted association of time-varying pneumonia (within 30 days post-fracture) with mortality and incidence of cardiovascular events 0–30, 31–365, and 366–730 days post-fracture. Results There was a high–early rate of pneumonia within 30 days post-fracture for young, middle-aged, and elderly adults with intellectual disabilities (n = 6,183); this rate was 2.2- to 6.1-fold higher than the rate among the w/oFx (n = 12,366) and GP+Fx (n = 363,995) cohorts (all P < 0.05). For the Fx cohort, post-fracture 30-day incidence of pneumonia was associated with an increased 30-day rate of mortality (adjusted HR [aHR] = 5.19; 95% confidence interval [CI] = 3.68–7.32), heart failure (aHR = 2.96; 95% CI = 1.92–4.56), and cerebrovascular disease (aHF = 1.48; 95% CI = 0.93–2.35; P = 0.098), with sustained effects to 1 year for heart failure (aHR = 1.61; 95% CI = 1.19–2.17) and 2 years for mortality (aHR = 1.39; 95% CI = 1.06–1.83), and without evidence of effect modification by age. Discussion Adults with intellectual disabilities are vulnerable to post-fracture pneumonia within 30 days, and complications arising from this, across the adult lifespan, and not only during the elderly years.